Biologically Targeted Therapy of Pediatric Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Investigators at the Mayo Clinic, Rochester, MN; George Washington University, and Children's National Brain Tumor Institute, Washington, DC review the molecular pathways implicated in pediatric brain tumors, biologic agents that target these pathways, and current clinical trials of these novel therapies.